The psychological experience of being in hiding against the background of political repression in South Africa during the 1986 general State of Emergency: a phenomenological explication - Scheepers, Esca (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
This is a study in Critical Psychology which examines the psychological costs of one of the direct outcomes of political repression - the experience of being in hiding. The aims of the study can be depicted on two levels: it is first and foremost an attempt to provide a true account of the phenomenon of being in hiding. On a second level of equal importance it is an implicit and overt critique of the social order in which this phenomenon takes place. The psychological experience of being in hiding is examined and discussed in its proper socio-political context. Therefore, the theoretical part of the mini-thesis has a strong political bearing, focusing on the State, and extra-parliamentary opposition in South Africa. repression The empirical part of the mini-thesis explicates the psychological experience of being in hiding with the aid of the phenomenological method of investigation. Due to the lack of research on this or similar topics, it is discussed within the framework of the experience of a stressful life event. For the five subjects being in hiding was an extreme intervention which was imposed upon their existences and which brought about a qualitative transformation in the individual subjects mode of being-in-the-world - not only in terms of practicalities, but also on a deep experiential level. It was a phenomenon which touched on fundamental parts of their experience of themselves and their individual worlds and the way in which they actualized themselves. For them it essentially entailed a loss of relationships and roles which resulted in an experience of a measure of encapsulation or separation from the world of others . It was a profound, multi - dimensional disruption of the structure of the subject ' s existence which infused a rich emotional experience .
Keywords: Violence -- South Africa -- Psychological aspects; South Africa -- Politics and government -- 1989-1994